Effect of Muscle Energy Technology on Motor Dysfunction in Patients with Active Ankylosing Spondylitis - Hui OUYANG; Longbin SHEN; Xuechang HE; Zhenping LIN (康复学报)
Objective:To observe the effect of muscle energy technology (MET) on the pain, range of motion, muscle strength and inflammatory indicators in patients with active ankylosing spondylitis (AS), and to seek an effective physical therapy to improve dysfunction in AS patients.Methods:Twenty-four patients with active AS confirmed by the rheumatologists were randomized into experimental group (n=10) and control group (n=14). The experimental group accepted both conventional drug treatment (celecoxib) and MET therapy, and the control group accepted only celecoxib. The treatment lasted for three months in both groups. The MET therapy adopted various techniques targeting at different dysfunctional points that identified by visual analog scale (VAS) score. A number of measures were evaluated before and after the treatment, including pain assessment by VAS, rang of motion (ROM), manual muscle testing (MMT), ankylosing spondylitis schober test, bath AS disease activity index (BASDAI), bath AS functional index (BASFI), erythrocyte sedimentation rate (ESR) and c-reactive protein (CRP) level.Results:After the treatment, the VAS, BASFI, BASDAI, ESR, and CRP in experimental group were decreased significantly, while muscle strength, cervical ROM, thoracic ROM, lumbar ROM and Schober score were increased significantly (P<0.05). The VAS and ESR in control group were decreased significantly (P<0.05). Compared with the control group, the pain VAS, BASFI and BASDAI scores were decreased significantly, muscle strength, lumbar ROM and Schober score were increased significantly (P<0.05).Conclusion:MET is an effective therapy in reducing pain and improving the lumbar joint mobility, muscle strength and AS functional index for AS patients at the active stage.